춤의 정체성 논의와 실제 - <백조의 호수> 사례를 중심으로 - 김운미 (한국무용기록학회지, 2011)
2000년대 들어 무용에서도 저작권에 대한 개념이 생기고 분쟁이 일어나고 있다. 무용은 시간성을 가진 예술이다. 따라서 저작권 개념은 이 공연과 저 공연의 차이, 오늘의 공연과 어제의 공연 그리고 더 확장된다면 어제의 공연과 10년·100년 전의 공연까지도 같은 공연인지에 대한 무용의 근본적인 정체성에 대한 의문으로 이어진다. 어떠한 기준으로 같은 공연과 다른 공연을 판별할 수 있는지를 살펴보기 위해 넬슨 굿맨(Nelson Goodman)의 춤의 자필적/대필적 속성과 리처드 월하임(Richard Wolheim)의 공연예술에서의 유형과 징표를 기초 개념을 이론적 배경으로 하였다. 그리고 이것을 유리 그리가로비치(Yuri Grigorovich)의 작품 <백조의 호수>에 적용하여 실체화 하였다. 두 작품의 비교는 춤에서 동일성을 확보해줄 정체성을 찾기 위한 사례 연구이다. 1984년작과 2008년작 두 공연물을 비교한 결과 첫째, 춤에서 최초의 공연은 유형을 창출하는 징표로 작용함을 알 수 있었다. 둘째, 두 공연에서 약간의 동작 차이는 있지만 발레에서 디베르 티스망의 속성 상 유의미한 변화라고 보기는 어렵다. 셋째, 춤은 같은 안무가의 작품이라도 시대에 따라 미묘한 차이를 보이며 공연이 변모하고 있음을 확인하였다. 이와 같이 본고의 사례가 다른 작품에 일괄적으로 적용되는데는 한계가 있지만 춤의 정체성을 찾는데 일부 기준점으로 적용할 수 있겠다. The idea of copyrighting a dance work has been in dispute in the dance field since 2000. Dance is an art including time nature. Therefore, the concept of a copyright has raised doubts on the differences between this performance and that performance; yesterday`s performance and today`s performance; yesterday`s performance and the performance of 10 years ago or of 100 years ago. We can debate whether these performances are the same work or not. These questions make us doubt the radical identity of dance. I applied Nelson Goodman`s autographi/allographic properties and Richard Wolheim`s type and token of performing arts for this research. And it is emerged in Yuri Grigorovich`s . Comparison of two performances is a case study to find out an identity which secures the sameness of them. I compared two performances and drew the following conclusion. First, the first performance flows into the next one as a token which creates a kind of type. Secondly, there are some differences between the two performances but the movement would not be considered as meaningful change because divertissement in ballet is a part which show dancer`s technique off. Thirdly, although two performances are the same choreographer`s works, dance movements have been changed as time goes by. This case study has limitations. Therefore, these criteria can not be applied en bloc. However, this case can be used criteria to find out identity of dance.
Keywords: 춤; 공연예술; 정체성; 동일성; 백조의 호수